2020
DOI: 10.1111/echo.14582
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic assessment of left ventricular function recovery post percutaneous coronary intervention of chronic total occlusions in patients with low and mid‐range left ventricular ejection fractions

Abstract: Objectives Coronary chronic total occlusion (CTO) is a frequent condition encountered in cardiac catheterization laboratory with a prevalence of about 20%. Through literature, data are scarcely reported regarding the left ventricular (LV) function recovery post CTO percutaneous coronary intervention (PCI) in patients with low (<40%) and mid‐range (40%‐49%) LV ejection fraction (LVEF). The aim of this study was to assess the echocardiographic outcomes of CTO patients with low and mid‐range LVEF successfully rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Samy M et al found that left ventricular ejection fraction improvement after successful PCI was signi cantly more in patient with lower ejection fraction group. [25] Galassi AR et al also reported that successful revascularization in patients with left ventricular ejection fraction < 35% improved left ventricular ejection fraction and 2 years all-cause mortality. [26] Moreover, successful PCI was associated with better cardiac survival in elderly especially when complete revascularization is achieved.…”
Section: Discussionmentioning
confidence: 95%
“…Samy M et al found that left ventricular ejection fraction improvement after successful PCI was signi cantly more in patient with lower ejection fraction group. [25] Galassi AR et al also reported that successful revascularization in patients with left ventricular ejection fraction < 35% improved left ventricular ejection fraction and 2 years all-cause mortality. [26] Moreover, successful PCI was associated with better cardiac survival in elderly especially when complete revascularization is achieved.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, diabetes patients were older (mean age was 70 years old) and there was high prevalence of chronic kidney disease and heart failure with reduced ejection fraction. Samy et al found that left ventricular ejection fraction improvement after successful PCI was significantly more in patient with lower ejection fraction group [25]. Galassi et al also reported that successful revascularization in patients with left ventricular ejection fraction ≤ 35% improved left ventricular ejection fraction and 2 years all-cause mortality [26].…”
Section: Discussionmentioning
confidence: 99%
“…The amount of viable myocardium viability in the CTO-related territory can have an influence on LVEF, and successful revascularization was associated with the recovery of hibernating myocardium and reduction in adverse left ventricular remodeling. Depressed LVEF is well-known to be associated with increased risk of MACEs, and the improvement of LVEF increased electrical stability, reduced ventricular arrhythmias (a main reason for cardiac death), and provided the collateral vessels with protection against future adverse events (34).…”
Section: Discussionmentioning
confidence: 99%